2003
DOI: 10.1016/s0965-8564(02)00021-6
|View full text |Cite
|
Sign up to set email alerts
|

Drivers’ willingness-to-pay to reduce travel time: evidence from the San Diego I-15 congestion pricing project

Abstract: The adoption of congestion pricing depends fundamentally upon drivers' willingness to pay to reduce travel time during the congested morning peak period. Using revealed preference data from a congestion pricing demonstration project in San Diego, we estimate that willingness to pay to reduce congested travel time is higher than previous stated preference results. Our estimate of median willingness to pay to reduce commute time is roughly $ 30 per hour, although this may be biased upward by drivers' perception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(104 citation statements)
references
References 10 publications
4
98
0
2
Order By: Relevance
“…Some empirical studies have specifically addressed the non-constancy of value of time, e.g., Calfee and Winston [4] Brownstone et al [2], and others. Their estimates are based on discrete choice analysis, e.g., Small and Rosen [12] and Anderson et al [1].…”
Section: Introductionmentioning
confidence: 99%
“…Some empirical studies have specifically addressed the non-constancy of value of time, e.g., Calfee and Winston [4] Brownstone et al [2], and others. Their estimates are based on discrete choice analysis, e.g., Small and Rosen [12] and Anderson et al [1].…”
Section: Introductionmentioning
confidence: 99%
“…Most SP surveys have a similar structure as was used in presentation two where time is saved as a result of paying a fee, in most cases a toll, but in this case, a single use permit. Brownstone et al (2003) have noted that SP studies generally yield lower values than RP studies. Avoidance of paying additional fees for a public good that people believe they had already paid for in the form of taxes may explain this underestimate.…”
Section: Resultsmentioning
confidence: 99%
“…Brownstone et al (2003) found that the choice of I-15 FasTrak (tolled trip) in San Diego was related to travel time savings and pricing. Golob, 2001 found that the choice of I-15 Express Lanes was related to the level of the perceived safety advantage of I-15 Express Lanes travel.…”
Section: Chapter II Literature Reviewmentioning
confidence: 99%